2019
DOI: 10.1002/nop2.435
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' perceptions of patient safety for the woman in childbirth in Sweden – An interview study

Abstract: Aim To describe healthcare professionals' perceptions of patient safety with a focus on the woman in connection to childbirth. Design A descriptive and qualitative design with a phenomenographic approach. Methods Individual qualitative face‐to‐face interviews with 19 healthcare professionals (midwives, nursing assistants and physicians) were conducted in three labour wards in Sweden. The data were analysed according to Dahlgren and Fallsberg's seven steps. Results The informants' perceptions of patient safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The team competence 'Situation monitoring' reflects the process of actively scanning and assessing situational elements to gain information or understanding or to maintain awareness to support team functioning [36]. A tolerant atmosphere in the labor ward leads team members to exchange relevant information and dare to speak up to strengthen patient safety [27]. 'Communication' is the structured process by which information is clearly and accurately exchanged among team members [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The team competence 'Situation monitoring' reflects the process of actively scanning and assessing situational elements to gain information or understanding or to maintain awareness to support team functioning [36]. A tolerant atmosphere in the labor ward leads team members to exchange relevant information and dare to speak up to strengthen patient safety [27]. 'Communication' is the structured process by which information is clearly and accurately exchanged among team members [38].…”
Section: Discussionmentioning
confidence: 99%
“…'Communication' is the structured process by which information is clearly and accurately exchanged among team members [38]. In labor wards, using the SBAR (Situation, Background, Assessment, Recommendation) at handovers and during rounds decreased the risk for missing information [27]. The differences between the labor wards are difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that women who sustained severe perineal lacerations suffered physically and psychologically and were not satisfied with their healthcare support [ 7 , 43 ]. Professional support in terms of a midwife being present in the labor room is important to create safe conditions during childbirth and can lead to decreased anxiety and tension in women [ 44 ]. Supportive care includes emotional support, information, advice about coping practices and comfort procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts made by health services to promote patient safety, nursing is still susceptible to various care malpractices (1) . The failure, unlike a violation, is not an intentional result and can be interpreted as inherent in the human condition, even if unwanted (2) . In the health sector, the occurrence of the malpractice is strictly related to the failure of processes and implies the need to adopt systemic measures that promote a safe environment for care (2)(3) .…”
Section: Introductionmentioning
confidence: 99%